OPTIMASI PARAMETER PEMOTONGAN MESIN BUBUT CNC TERHADAP KEKASARAN PERMUKAAN DENGAN RESPONSE SURFACE METHODOLOGY (RSM) PADA MATERIAL Al-6061 - Sudjatmiko Sudjatmiko; Darto Darto; Rusdijianto Rusdijianto (Universitas Lambung Mangkurat, 2015)
Research lathe machining process, carried out on workpiece material T-6061 aluminum and the HSS. The problem is that a large beaker radiuschip, spindle rotation and eat optimum motion to produce lathe Al-6061 with a surface that is smooth, safe and capable of producing a high production capacity with a cutting depth (depth of cut) is constant.Optimized cutting parameters selection is very important to control the quality of the product surface cylindrical form of Al-6061 is to optimize for spindle rotation, movements meal and corner radius (Chip) furious breaker using two measures of performance, metal removal rate and the surface roughness.Response Surface Methodology (RSM). Alleged best regression model to speed snarled income (MRR) at a rate of 95% at n = 900 rpm, f = 115 mm / put and RCB = 1.25 mm is = . While allegations of the best regression model for surface roughness (SR) at a rate of 95% at n = 900 rpm, f = 115 mm / put and RCB = 1.25 mm adalah: +0,14x2x3. A regression model be able to describe the relationship between the combination of cutting parameters and radius chip breaker produced maximum metal removal rate and minimum surface roughness. Spindle rotation is the dominant influence on the surface roughness, whereas eating motion and spindle rotation is very influential on the metal removal rate, followed by radius chip breaker. Results obtained by iterative optimization using Response Optimizer for surface roughness (SR) at n = 950 rpm, f = 90 mm / put and RCB = 1.44 mm resulted SR 0.360 μm, while the Response Optimizer on MRR at n = 950 rpm, f = 90 mm / put and RCB generate MRR = 1.44 mm 39.55 mm 3 / sec. Key words : Material Removal Rate,Optimizer Response, chip breaker, surface roughness